“El Patio de los Vientos Perdidos” by Roberto Burgos Cantor: Aspects of the Novel of the Enchantment Of Interiority - Orduz Rodríguez, Frank Alexander (2022)
This article studies El patio de los vientos perdidos (1984), the first novel by Colombian writer Roberto Burgos Cantor. From the parameters of The novel of the enchantment of interiority, a category proposed by Hélène Pouliquen (2018), it shows how the moments of plenitude oppose radical skepticism. Thus, it examines how paradigms that organize an ethic of interiority operate in the novel, where the characters experience moments of fullness despite their difficult realities.